Structural optical and electrical properties of a transparent conductive ITO/Al–Ag/ITO multilayer contact - Isiyaku, Aliyu Kabiru; Ali, Ahmad Hadi; Nayan, Nafarizal (Beilstein Journal of Nanotechnology, 2020)
Indium tin oxide (ITO) is a widely used material for transparent conductive oxide (TCO) films due to its good optical and electrical properties. Improving the optoelectronic properties of ITO films with reduced thickness is crucial and quite challenging. ITO-based multilayer films with an aluminium–silver (Al–Ag) interlayer (ITO/Al–Ag/ITO) and a pure ITO layer (as reference) were prepared by RF and DC sputtering. The microstructural, optical and electrical properties of the ITO/Al–Ag/ITO (IAAI) films were investigated before and after annealing at 400 °C. X-ray diffraction measurements show that the insertion of the Al–Ag intermediate bilayer led to the crystallization of an Ag interlayer even at the as-deposited stage. Peaks attributed to ITO(222), Ag(111) and Al(200) were observed after annealing, indicating an enhancement in crystallinity of the multilayer films. The annealed IAAI film exhibited a remarkable improvement in optical transmittance (86.1%) with a very low sheet resistance of 2.93 Ω/sq. The carrier concentration increased more than twice when the Al–Ag layer was inserted between the ITO layers. The figure of merit of the IAAI multilayer contact has been found to be high at 76.4 × 10−3 Ω−1 compared to a pure ITO contact (69.4 × 10−3 Ω−1). These highly conductive and transparent ITO films with Al–Ag interlayer can be a promising contact for low-resistance optoelectronics devices.
Keywords: annealing; DC sputtering; figure of merit; indium tin oxide (ITO); multilayer structure; RF sputtering

(untitled) - Zhou, S.; Cao, B.; Liu, S.; Ding, H. (Opt. Laser Technol., 2012)

(untitled) - Balestrieri, M.; Pysch, D.; Becker, J.-P.; Hermle, M.; Warta, W.; Glunz, S. W. (Sol. Energy Mater. Sol. Cells, 2011)

(untitled) - Indluru, A.; Alford, T. L. (J. Appl. Phys., 2009)

(untitled) - Meshram, N.; Loka, C.; Park, K. R.; Lee, K.-S. (Mater. Lett., 2015)

(untitled) - Lippens, P.; Büchel, M.; Chiu, D.; Szepesi, C. (Thin Solid Films, 2013)

(untitled) - Song, S.; Yang, T.; Li, Y.; Pang, Z.; Lin, L.; Lv, M.; Han, S. (Vacuum, 2009)

(untitled) - Guillén, C.; Herrero, J. (Thin Solid Films, 2011)

(untitled) - Chakaroun, M.; Lucas, B.; Ratier, B.; Aldissi, M. (Energy Procedia, 2012)

(untitled) - Kumar, M. D.; Park, Y. C.; Kim, J. (Superlattices Microstruct., 2015)

(untitled) - Guillén, C.; Herrero, J. (Sol. Energy Mater. Sol. Cells, 2008)

(untitled) - Bou, A.; Torchio, P.; Barakel, D.; Guillou, A.; Ayachi, B.; Thoulon, P.-Y.; Ricci, M. (J. Phys. D: Appl. Phys., 2015)

(untitled) - Lin, T.-C.; Huang, W.-C.; Tsai, F.-C. (Microelectron. Eng., 2017)

Ultrathin Metal Transparent Electrodes for the Optoelectronics Industry - Ghosh, D. S. (Basics of Ultrathin Metal Films and Their Use as Transparent Electrodes, 2013)

(untitled) - Ali, A. H.; Hassan, Z.; Shuhaimi, A. (J. Alloys Compd., 2016)

(untitled) - Li, Y.; Liduo, W.; Chun, C.; Lian, D.; Yong, Q. (Chin. Sci. Bull., 2004)

(untitled) - Kim, D. (Appl. Surf. Sci., 2010)

(untitled) - Lin, Y. C.; Chang, S. J.; Su, Y. K.; Tsai, T. Y.; Chang, C. S.; Shei, S. C.; Kuo, C. W.; Chen, S. C. (Solid-State Electron., 2003)

(untitled) - Muralidhar Singh, M.; Vijaya, G.; Krupashankara, M. S.; Sridhara, B. K.; Shridhar, T. N. (Mater. Today: Proc., 2018)

(untitled) - Mwema, F. M.; Oladijo, O. P.; Akinlabi, S. A.; Akinlabi, E. T. (J. Alloys Compd., 2018)

(untitled) - Quintana, P.; Oliva, A. I.; Ceh, O.; Corona, J. E.; Aguilar, M. (Superficies Vacio, 1999)

(untitled) - Isiyaku, A. K.; Ali, A. H.; Ramly, N. F. (Mater. Today: Proc., 2019)

The 4th IEEE International NanoElectronics Conference - Chiu, P. K.; Cho, W. H.; Chen, H. P.; Hsiao, C. N.; Yang, J. R. (Study on sandwich structure of the transparent conducting oxide films prepared by electron beam evaporation at room temperature, 2011)

(untitled) - Jeong, J.-A.; Kim, H.-K.; Yi, M.-S. (Appl. Phys. Lett., 2008)

(untitled) - Park, Y.-S.; Park, H.-K.; Jeong, J.-A.; Kim, H.-K.; Choi, K.-H.; Na, S.-I.; Kim, D.-Y. (J. Electrochem. Soc., 2009)

(untitled) - Kudo, E.; Hibiya, S.; Kawamura, M.; Kiba, T.; Abe, Y.; Kim, K. H.; Sugiyama, T.; Murotani, H. (Thin Solid Films, 2018)

(untitled) - Loka, C.; Yu, H. T.; Lee, K.-S. (Jpn. J. Appl. Phys., 2014)

(untitled) - Gulen, M.; Yildirim, G.; Bal, S.; Varilci, A.; Belenli, I.; Oz, M. (J. Mater. Sci.: Mater. Electron., 2013)

(untitled) - Jeong, J.-A.; Kim, H.-K.; Koo, H.-W.; Kim, T.-W. (Appl. Phys. Lett., 2013)

(untitled) - Cho, E. N.; Moon, P.; Kim, C. E.; Yun, I. (Expert Syst. Appl., 2012)

(untitled) - Roh, H.-S.; Cho, S.-H.; Lee, W.-J. (Phys. Status Solidi A, 2010)

(untitled) - Kim, H.-J.; Lee, H. H.; Kal, J.; Hahn, J.; Kim, H.-K. (AIP Adv., 2015)

(untitled) - Balasundaraprabhu, R.; Monakhov, E. V.; Muthukumarasamy, N.; Nilsen, O.; Svensson, B. G. (Mater. Chem. Phys., 2009)

(untitled) - Liu, W.-S.; Cheng, H.-M.; Hu, H.-C.; Li, Y.-T.; Huang, S.-D.; Yu, H.-W.; Pu, N.-W.; Liang, S.-C. (Appl. Surf. Sci., 2015)

(untitled) - Ali, A. H.; Shuhaimi, A.; Hassan, Z. (Appl. Surf. Sci., 2014)

(untitled) - Hu, Y.; Diao, X.; Wang, C.; Hao, W.; Wang, T. (Vacuum, 2004)

(untitled) - Zhao, X.; Li, H.; Yang, K.; Jiang, S.; Jiang, H.; Zhang, W. (J. Alloys Compd., 2017)

(untitled) - Ghorannevis, Z.; Akbarnejad, E.; Ghoranneviss, M. (J. Theor. Appl. Phys., 2015)

(untitled) - Guillén, C.; Herrero, J. (J. Appl. Phys., 2007)

(untitled) - Ding, X.; Yan, J.; Li, T.; Zhang, L. (Appl. Surf. Sci., 2012)

(untitled) - Haacke, G. (J. Appl. Phys., 1976)